Risk, vulnerability and impact perception: an overview considering water systems using collaborative methods and mathematical modelling - Reis, Gabriela de Azevedo (2023)
Drought events are a significant concern, and proactive strategies are required to mitigate their impact, such as the evaluation of vulnerabilities, risks and impacts. The participatory process in water resources planning and management is established in several nations, but vulnerability and risk analysis often remain one-sided. To effectively manage water resources, an interdisciplinary approach is necessary. This work provides different methods that comprehends the contribution of collaborators’ knowledge and experience in order to asses vulnerabilities, risks and impacts in a drought scenario. The iSECA is a MCDM GIS-based index, characterized as a straightforward and accessible tool for quantifying vulnerability to drought caused by climate change, considering social, economic, and water management aspects. This model was applied to the Brazilian states of Ceará and São Paulo, identifying vulnerable locations and areas with water infrastructure that can improve local and regional adaptive capacity. The model results are clear and easy to understand and can serve as an indispensable tool for water management and drought planning. The methodology does not require fieldwork or extensive financial costs and can be applied at different scales for the development of plans such as drought and water security management. A typology of risks for water systems was developed through a collaborative process involving professionals with different experiences and expertise in water systems. The typology matrix classifies the types of structures of a water system against classes of risk to assist in risk assessment and decisionmaking. The typology is adaptable to different configurations of water systems and provides an important tool for water resource management. A fuzzy logic model is proposed to evaluate integrated risks of water systems using fuzzy logic and the typology of risks, which can handle qualitative information and quantify data. However, the data acquisition step is timeconsuming and can exacerbate the lack of information, affecting the final results. Nonetheless, this approach can aid decision-making for water system management. Lastly, we evaluate the drought impact perception of stakeholders of the river basins committees in order to analyze how they behave can influence the water allocation and decision-making process through network analysis.